POPULASI MONYET EKOR PANJANG (Macaca fascicularis) DI HUTAN LINDUNG DESA PULAU JAYA KECAMATAN TEMPUNAK KABUPATEN SINTANG - Sangkauw, Heriditus; Prayogo, Hari; Anwari, M Sofwan (JURNAL HUTAN LESTARI, 2019)
Protected Forest Areas in Pulau Jaya Village still have shifting cultivation activities. The shifting cultivation system that used Â has caused forest damage ecosystem which is habitat of long-tailed macaque.The study aim to determined the population and density of long-tailed macaque in Pulau Jaya Village, Tempunak sub-district, Sintang regency. The research on population of Long-tailed macaque was conducted four-month period strarted from february to june 2018. The survey was conduct by using track, there is five track that conducted survey. It was also conducted repeated three times surveys on 1000 meter length track. The result of this research shown that the total number of this long-tailed macaque is about 114 individu and 13 groups while the individual density is 0,0676 to 1,86 individu per hectare and the group density is 0,0806 to 0,2086 group per hectare.Keywords : Macaca fascicularis, Population, Pulau jaya village, secondary forest.